Penerapan Strategi Pembelajaran Active Knowledge Sharing untuk Meningkatkan Hasil Belajar Siswa pada Pelajaran IPA Terpadu SMP Negeri 1 Ulumoro’o Tahun Pembelajaran 2024/2025 - Andriwati Gulo (GEN BIONIX: Jurnal Ilmiah Pendidikan Biologi, 2024)
Low student learning outcomes in Integrated Science subjects remain a major problem in the learning process at schools, particularly because classroom instruction tends to be teacher-centered, causing students to be less active during learning activities. This study aimed to improve students’ learning outcomes through the implementation of the Active Knowledge Sharing learning strategy in Integrated Science at SMP Negeri 1 Ulumoro’o during the 2024/2025 academic year. This study employed a Classroom Action Research (CAR) approach conducted in two cycles, where each cycle consisted of planning, action, observation, and reflection stages. The research subjects were 30 students of class VII-A. The data were collected through observation, learning achievement tests, questionnaires, interviews, and documentation, then analyzed descriptively using quantitative and qualitative approaches. The findings revealed that the implementation of the Active Knowledge Sharing strategy improved both student learning activities and learning outcomes. The average student score increased from 64.44 in Cycle I to 77.50 in Cycle II, while the learning mastery percentage increased from 60% to 86.67%. In addition, the quality of learning improved from a fair category to a very good category. These findings indicate that the Active Knowledge Sharing strategy was effective in creating a more active, collaborative, and meaningful Integrated Science learning environment.